Applicability of Lewin’s Change Management Model for Optimization Management Function in Nursing Delegation between Head Nurse and Team Leader: A Mini Project in Jakarta Military Hospital - Aris Teguh Hidayat; Rr. Tutik Sri Hariyati Sri Hariyati; Titiek Muhaeriwati Muhaeriwati (Alta Dharma Publisher, 2020)
The role of nurses in healthcare systems is diverse, including being a health care provider to clients, client advocates, educators for clients and families, and nursing service managers. This study's goal was to assess Kurt Lewin's change management method to analyze the management function in nursing delegation between the head nurse and team leader. This project was conducted at Jakarta Military Hospital using a fishbone diagram approach, and solving problems using Plan-Do-Check-Action (PDCA) tools starting with Plan Of Action (POA), implementation, evaluation, and follow-up. The study results showed that the head nurse performed nonoptimal delegation in terms of delay to complete the nursing documentation, non-uniformity of delegation format, and lack of control from superiors. Guidelines are used as a reference in delegating nursing to the head of the hospital room. The documentation of nursing delegates is done because representatives work better when the reporting structure is clear. In conclusion, the application fishbone diagram, Lewin's change management model, and PDCA cycle can optimize management function in nursing delegation between head nurse and team leader in Jakarta Military Hospital. Recommendations are given to the nursing department, head of the room, team leader, and executive nurses to increase self-awareness, knowledge, and ability in delegating nursing.